Comparison of Arthropod Diversity in Organic and Conventional Rice Cultivation in Trawas District, Mojokerto Regency - Ayumi, Cicik Nur; Rahardjo, Bambang Tri (Journal of Tropical Plant Protection, 2024)
Different cultivation techniques for rice (Oryza sativa L.) are known to affect arthropod populations and diversity levels. This research was conducted to study how arthropod diversity can be affected by different cultivation techniques. The research was carried out from October 2022 to March 2023. Arthropod diversity observations were carried out in the organic rice field of Kampung Pertanian Organik Brenjonk and a conventional rice field belonging to a farmer in Penanggungan Village, Trawas District, Mojokerto Regency. Data were collected weekly for 12 observations. Arthropods were collected using passive methods, such as pitfall and yellow sticky traps, and active methods, such as sweep netting and handpicking. The data were analyzed to assess the diversity level. The results showed more arthropods in the organic rice field, with 1815 individuals consisting of 4 classes, 13 orders, 52 families, 70 genera, and 74 morphospecies. In contrast, in the conventional rice field, 1028 individuals were found, consisting of 3 classes, ten orders, 28 families, 32 genera, and 33 morphospecies. The calculation results of arthropod diversity levels showed that the organic field is better than the conventional field.